Effects of obesity on periodontal tissue remodeling during orthodontic movement - Marcantonio, Camila Chierici [UNESP]; Nogueira, Andressa Vilas Boas [UNESP]; Leguizam, Natalia Da Ponte [UNESP]; Molon, Rafael Scaf de [UNESP]; Lopes, Maria Eduarda Scordamaia [UNESP]; Silva, Renata Cristina Lima [UNESP]; Cerri, Paulo Sergio [UNESP]; Deschner, James; Cirelli, Joni Augusto [UNESP] (Elsevier B.V., 2021)
Introduction: Orthodontic movement triggers a sequence of cellular and molecular events that may be affected by different systemic conditions. This study evaluated the effect of obesity on rat periodontal tissue remodeling induced by mechanical orthodontic force. Methods: Thirty-two Holtzman rats were distributed into 4 groups: control, obesity induction (O), orthodontic movement (M), and obesity induction and orthodontic movement (OM). Obesity was induced by a high-fat diet for 90 days. After 15 days of orthodontic movement, the animals were killed. Obesity induction was confirmed by animal body weight, adipose tissue weight, and serologic analysis. Periodontal tissue remodeling was evaluated using microcomputed tomography and histologic analysis. The gene expression of adipokines and cytokines in gingival tissues was evaluated. Results: An increase in body and adipose tissue weight was observed in the obesity induction groups. The O group presented an increase in lipids and blood glucose. The OM group showed a decrease in bone volume fraction and bone mineral density compared with all other groups and a tendency for more rapid tooth movement than the M group. The OM group showed a higher quantity of inflammatory cells and higher Mmp1 expression than the O group. The O and OM groups showed higher Nampt expression than the control group and lower Nampt expression than the M group. Conclusions: Obesity modulates periodontal tissue remodeling during orthodontic movement and results in more inflammation and bone loss than in nonobese animals. (Am J Orthod Dentofacial Orthop